BlockFlex: Enabling Storage Harvesting with Software-Defined Flash in Modern Cloud Platforms - Reidys, Benjamin; Sun, Jinghan; Badam, Anirudh; Noghabi, Shadi; Huang, Jian (OSDI, 2022)
Cloud platforms today make efficient use of storage resources by slicing them among multi-tenant applications on demand. However, our study discloses that the cloud storage is still seriously underutilized for both allocated and unallocated storage. Although cloud providers have developed harvesting techniques to allow evictable virtual machines (VMs) to use unallocated resources, these techniques cannot be directly applied to storage resources, due to the lack of systematic support for isolation of space, bandwidth, and data security in storage devices.